Decrease of Lipid Oxidation for Dried Shrimp (Acetes chinensis) Preservation Using Alkaline Lipase Hydrolysis Technology. Issue 2 (17th February 2016) - Liu, Jianhua; Zhao, Peicheng; Liu, Lin; Zhang, Jianyou; Liu, Shulai; Zhang, Zhifei; Ding, Yuting
ABSTRACT: In this study, the degreasing technology using alkaline lipase hydrolysis for Chinese dried shrimp ( Acetes chinensis ) was investigated, with the purpose of decreasing lipid oxidation during dried shrimp preservation. The salt, moisture, and lipid contents of the shrimp were 6.01, 32.51, and 2.95%, respectively. The optimum enzymatic hydrolysis condition for effective decrease of shrimp lipid was obtained: lipase concentration 40 U/mL, pH 10, soaking time 60 min, soaking temperature 30°C, and shrimp/liquid ratio 1:20 (w:v). Under this optimum condition, the residual lipid of the shrimp was reduced to 2.28%, and the degreasing rate reached 49%. During 30-day preservation, the thiobarbituric acid-reactive substances (TBARS) value (0.185 mg/kg of dried shrimp and 0.131 mg/kg of degreased dried shrimp at Day 30) of degreased shrimp was lower than the shrimp without degreasing, indicating alkaline lipase hydrolysis could effectively prevent lipid oxidation and inhibit oxidative rancidity during dried shrimp preservation.